A flagellin-conjugate protein induces dual NLRC4- and NLRP3-inflammasome activation which modulates inflammatory cytokine secretion from macrophages - Lin, Yen-Ju; Jamin, Annette; Wolfheimer, Sonja; Fiedler, Anna; Junker, Ann-Christine; Goretzki, Alexandra; Scheurer, Stephan; Schülke, Stefan (Frontiers in Immunology, 2023)
Background: A recombinant fusion protein combining the adjuvant and TLR5-ligand flagellin with the major birch pollen allergen Bet v 1 (rFlaA:Betv1) has been suggested to prevent the manifestation of birch allergy. Noteworthy, rFlaA:Betv1 induced both pro- and anti-inflammatory responses which were differentially regulated. However, the mechanism by which flagellin fusion proteins modulate allergen-specific immune responses, especially the mechanisms underlying IL-1β secretion and their contribution to the overall immune responses remains elusive. Objective: To investigate the mechanisms underlying the production of IL-1β from rFlaA:Betv1 stimulated macrophages. Methods: Macrophages were derived from mouse peritoneal-, human buffy-coat-, and PMA-differentiated THP-1 (wild type or lacking either ASC, NLRP3, or NLRC4) cells. Macrophages were stimulated with non-modified rFlaA:Betv1, mutant variants lacking either the flagellin DC0 domain or a sequence motif formerly described to mediate TLR5-activation, and respective controls in the presence or absence of inhibitors interfering with MAPK- and NF𝜅B-signaling. Cytokine secretion was analyzed by ELISA and intracellular signaling by Western Blot. To study the contribution of IL-1β to the overall immune responses, IL1R-deficient mouse peritoneal macrophages were used. Results: rFlaA:Betv1 consistently activated all types of investigated macrophages, inducing higher IL-1β secretion compared with the equimolar mixture of both proteins. rFlaA:Betv1-induced activation of THP-1 macrophages was shown to be independent of either the TLR5-activating sequence motif or the flagellin DC0 domain, but depended on both NLRP3- and NLRC4-inflammasomes. In addition, NFκB and SAP/JNK MAP kinases regulated rFlaA:Betv1-induced inflammasome activation and cytokine secretion by modulating pro-Caspase-1- and pro-IL-1β-expression in THP-1 macrophages. Finally, lack of IL-1β positive feedback via the IL1R strongly diminished the rFlaA:Betv1-induced secretion of IL-1β, IL-6, and TNF-α from peritoneal macrophages. Conclusion: The mechanisms contributing to rFlaA:Betv1-induced IL-1β secretion from macrophages were shown to be complex, involving both NLRC4- and NLRP3-inflammsomes, as well as NFκB- and SAP/JNK MAP kinase-signaling. Better understanding the mechanisms regulating the activation of immune cells by novel therapeutic candidates like the rFlaA:Betv1 fusion protein will allow us to further improve and develop new treatment strategies when using flagellin as an adjuvant.